Antiretroviral Long-Term Efficacy and Resistance of Lopinavir/Ritonavir Plus Lamivudine in HIV-1-Infected Treatment-Naïve Patients (ALTERLL): 144-Week Results of a Randomized, Open-Label, Non-Inferiority Study From Guangdong, China - Guo, Peng-Le; He, Hao-Lan; Chen, Xie-Jie; Chen, Jin-Feng; Chen, Xiao-Ting; Lan, Yun; Wang, Jian; Du, Pei-Shan; Zhong, Huo-Lin; Li, Hong; Liu, Cong; Li, Li-Ya; et al. (Frontiers in Pharmacology, 2021)
Methods: A randomized, controlled, open-label, non-inferiority trial (ALTERLL) was conducted to assess the efficacy, drug resistance, and safety of dual therapy with LPV/r plus 3TC (DT group), compared with the first-line triple-therapy regimen containing tenofovir (TDF), 3TC plus efavirenz (EFV) (TT group) in antiretroviral therapy (ART)-naïve HIV-1 infected adults in Guangdong, China. The primary endpoint was the proportion of patients with plasma HIV-1 RNA<50 copies/mL at week 144. Results: Between May 1st and December 31st 2015, a total of 196 patients screened from 274 ones were eligible and randomly assigned to either DT group (n = 99) or TT group (n = 97). In the primary (intention-to-treat, ITT) analysis at week 144, 95 patients (96%) in DT group and 93 patients (95.9%) in TT group had plasma HIV-1 RNA<50 copies/ml (difference: 0.1% [95%CI: -4.6% to 4.7%]), meeting the criteria for non-inferiority; DT group did not show significant differences in the mean increases in CD4+ cell count (247.0 vs 204.5 cells/mm3, P=0.074) or CD4/CD8 ratio (0.47 vs 0.49, P=0.947) from baseline nor the inflammatory biomarker levels through week 144 compared with the TT group. For the subgroup analysis, baseline high viremia (HIV-1 RNA>100,000 copies/ml) and genotype BC did not affect the primary endpoint nor the mean increases in CD4+ cell count or CD4/CD8 ratio from baseline at week 144; however, for patients with genotype AE, DT group showed higher mean increase in CD4+ cell count from baseline through 144 weeks compared with TT group (308.7 vs 209.4 cells/mm3, P=0.038). No secondary HIV resistance was observed in both groups. Moreover, no severe adverse event (SAE) or death was observed in both groups but more patients in TT group (6.1%) discontinued the assigned regimen than in DT group (1%) due to adverse event. Conclusion: Dual therapy with LPV/r plus 3TC manifests long-term non-inferior therapeutic efficacy, low drug resistance, good safety, and tolerability compared with the first-line triple-therapy regimen in Guangdong, China, indicating dual therapy is a viable alternative in resource-limited areas.